PERANAN SAKSI DALAM PERKARA PIDANA DILIHAT DARI UU NO.8 TAHUN 1981 - Iman Hidayat (Jurnal LEX SPECIALIS, 2010)
AbstractImplementation of Criminal Justice is the enforcement mechanism of the workings of the criminal law began the process of the investigation, arrest and detention, prosecution and trial examination, and the implementation of court decisions. Witnesses presented before the trial was not enough that only one witness, because a witness not a witness (Unus testis nulus testis), it is in KUHAP for in Article 185 paragraph (20), paragraph (3), and paragraph (4), namely that the testimony of a witness is not sufficient to prove that the defendant is guilty of acts that indicted him unless there are other valid evidence and witness testimony is required between these must relate to one another.